Synthesis and Biological Assessment of PyrimidoTacrines as Promising Agents for Alzheimer's Disease Therapy. Issue 37 (4th October 2021) - Dakhlaoui, Imen; Maalej, Emna; Martin, Helene; Lucht, Aurélia; Iriepa, Isabel; Moraleda, Ignacio; Marco‐Contelles, Jose; Chabchoub, Fakher; Ismaili, Lhassane
Abstract: Considering the multifactorial nature of Alzheimer's disease (AD), multitarget small molecules (MTSMs) represent the most potent and attractive therapeutic strategy to design new drugs for Alzheimer's disease therapy. Thus, new Pyrimidotacrines were designed and synthesized by merging pyrimidine scaffold and tacrine. Among them, 4‐(4‐nitrophenyl)‐2‐phenyl‐6, 7, 8, 9‐tetrahydropyrimido[4, 5‐b]quinolin‐5‐amine (4 j ) was identified as less hepatotoxic than tacrine at high concentration, a submicromolar inhibitor against both acetylcholinesterase (AChE) (IC50 =677±28 nM) and butyrylcholinesterase (BuChE) (IC50 =756±41 nM) showing potent antioxidant properties (2.43 TE) and displaying a strong neuroprotection effect against hydrogen peroxide (H2 O2 ) and Oligomycin Rotenone. Consequently, 4 j is a potential new hit‐ligand for AD therapy for further biological exploration Abstract : The combination of the multi‐targeted small molecule strategy and the interest of the tacrine scaffold allows the preparation of non‐hepatotoxic tacrine derivatives showing inhibition of ChEs such as the novel Pyrimidotacrines described here. In fact, compound 4 j was identified as less hepatotoxic than tacrine at a higher concentration, a submicromolar inhibitor against both AChE (IC50 =677 ± 28 nM) and BuChE (IC50 =756 ± 41 nM) showing potent antioxidant properties (2.43 TE) and displaying a strong neuroprotection effect against H2 O2 and the Oligomycin/Rotenone cocktail.